Interactive Video of Rigid Body Equilibrium in Lamongan Boranan Dance - Zaki Alhusni, Hanan; Astutik, Widi; Anggaryani, Mita; Saputra, Oka; Saphira, Hanandita Veda; Nasution, Nabila Nur Almaida (JPPS (Jurnal Penelitian Pendidikan Sains), 2024)
Objective:  This study aims to develop interactive video learning media that integrates rigid body equilibrium material in the context of Boranan Lamongan Dance, in order to improve students' understanding of abstract physics concepts while introducing local culture. Method: This study uses the ADDIE (Analysis, Design, Development) development method and was conducted at the high school level involving 3 physics teachers and 21 students.  At the analysis stage, the need for learning media that is relevant to the material and local context was identified. The design stage includes the creation of an interactive video that presents an explanation of rigid body equilibrium through Boranan Dance visualization. At the development stage, the video was tested on a limited basis to obtain feedback. The assessment in this response observation gform uses a Likert scale score. Results: The results of the study showed that this media was effective in improving understanding of the material with a percentage score of 84.57%, which indicates that this learning media is very effective according to the responses of teachers and students. In addition, this video also succeeded in integrating local wisdom, increasing students' learning motivation, and introducing local culture in an interesting way. Novelty: The uniqueness of this study lies in the combination of local cultural elements with physics material that is often considered abstract, as well as the use of interactive video as a fun and participatory learning tool. This research contributes to the development of technology-based learning media that prioritizes the preservation of local culture.